Superdiffusive transport in one-dimensional disordered Dirac model - Slavin, V.; Savin, Y. (Физика низких температур, 2018)
We have considered discrete one-dimensional Dirac equation in the framework of quantum dimer model with
Bernoulli distribution. It has been shown, that superdiffusive transport regime is realized at several combinations
of particle mass and amplitude of potential. For the case of non-zero mass it has been shown, that the only one
point exists, where Lyapunov exponent is equal to zero. In the framework of dimer model with “random masses”
it has been established, that localization is absent. Розглянуто одновимірне рівняння Дірака в рамках квантової
димерної моделі з розподілом Бернуллі. Показано, що при певних співвідношеннях маси частинки і амплітуди потенціалу
реалізується супердифузійний режим руху. У разі ненульовий
маси частки показано, що існує єдина точка, в якій показник
Ляпунова обертається в нуль. У рамках димерної моделі «випадкових мас» показано, що локалізація станів відсутня.
Ключові слова: низьковимірні системи, невпорядковані системи, супердифузійний транспорт, рівняння Дірака. Рассмотрено одномерное уравнение Дирака в рамках
квантовой димерной модели с распределением Бернулли.
Показано, что при определенных соотношениях массы частицы и амплитуды потенциала реализуется супердиффузионный режим движения. В случае ненулевой массы частицы
показано, что существует единственная точка, в которой
показатель Ляпунова обращается в нуль. В рамках димерной
модели «случайных масс» показано, что локализация состояний отсутствует.